KAJIAN KELAYAKAN PEMBENTUKAN DEIVISI PAKAN TERNAK PERUSAHAAN UMUM DAERAH ANEKA USAHA KABUPATEN DAIRI - Munthe, Kornel; Purba, Saut; Panjaitan, Ferry (UNIKA Santo Thomas, 2022)
The purpose of this study was to analyze the feasibility study of establishing a business for animal feed division from the production aspect, market aspect, organizational management aspect, and financial aspect. The data used in this study is secondary data obtained from Dairi Regency in terms of numbers and results of previous studies, while primary data is collected through questionnaires collected from the community and related OPD officials. The results of the analysis show that: (1) from the organizational management aspect, the production aspect, the technical and technological aspects and the market and marketing aspects and the socio-economic and financial aspects indicate that the establishment of an animal feed business division in Dairi Regency is feasible to be established and (2) the results of the analysis sensitivity with an increase in total production costs by 10% resulting in an NPV value >0, Net B/C >1, IRR> prevailing interest rates, and a payback period below 10 years and with a decrease in total income by producing an NPV value > 0, Net B/C >1, IRR>applicable interest rate and payback period below 10 years.